Wireless charging system for electric bicycle application - Nguyen Thi Diep; Nguyen Kien Trung; Tran Trong Minh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper presents a design of the wireless charging system for e-byke applications. The double-side LCC compensation circuit is used to achieve high efficiency and reduce the volt-ampere rating. A new constant current/voltage (CC/CV) charging control method at the transmitter side is proposed to avoid dual side wireless communication. This paper also presents a simple method of estimating both the coupling coefficient and load impedance only from the transmitter side. A wireless charging system of 2.5kW is built. Error in the CC/CV charging mode is 3.3% and 1.12%, respectively. System efficiency reaches 92.1% in CC charging mode.